Pooled analysis of 115 patients from updated data of Epitopes-HPV01 and Epitopes-HPV02 studies in first-line advanced anal squamous cell carcinoma. (December 2020) - Kim, Stefano; Meurisse, Aurélia; Spehner, Laurie; Stouvenot, Morgane; François, Eric; Buecher, Bruno; André, Thierry; Samalin, Emmanuelle; Jary, Marine; Nguyen, Thierry; El Hajbi, Farid; Baba-Hamed, Nabil; et al.
Aims: The addition of docetaxel to cisplatin and 5-fluorouracil (DCF) has shown promising efficacy in advanced squamous cell carcinoma of the anus (SCCA). Preliminary results of Epitopes-HPV01 study showed a high rate of long-lasting complete response to DCF. The prospective, multicenter, Epitopes-HPV02 trial then confirmed the high efficacy of the modified DCF (mDCF) regimen in terms of complete response rate and long-term survival in metastatic or non-resectable locally advanced recurrent SCCA. Here, we present updated results of the Epitopes-HPV01 and Epitopes-HPV02 studies. Patients & methods: Epitopes-HPV01 is a prospective study performed by the regional cancer network of Franche-Comté, France. Epitopes-HPV02 is a phase II study supported by two French collaborative oncological groups, performed in 25 centers. Both studies included patients with metastatic, or with unresectable local recurrent SCCA, treated with DCF regimen. Results: In Epitopes-HPV01, 51 patients were enrolled between September 2012 and January 2019, and 49 patients were included for analysis; while 69 patients were included between September 2014 and December 2016 in Epitopes-HPV02, and 66 patients for analysis. Pooled analysis of 115 patients showed a median progression-free survival of 12.2 months [95% confidence interval (CI) 10.6–16.1] [11.0 months (9.3–16.0) in -HPV02, and 15.6 months (11.2–34.5) in -HPV01, ( p = 0.06)]. The median overall survival was 39.2 months (26.0–109.1) [36.3 in -HPV02 (25.2–NR), and 61.1 months (21.4–120.0) in -HPV01 ( p = 0.62)]. Objective response rate was 87.7% (90.9% in -HPV02 and 83.3% in -HPV01) with 40.3% of complete response (45.5% in -HPV02 and 33.3% in -HPV01). No differences were observed between standard DCF ( n = 54) and mDCF ( n = 58) in terms of OS ( p = 0.57) and PFS ( p = 0.99). 5-years PFS and OS rates were 24.5% and 44.4%, respectively, in the whole population. No treatment-related death was observed. Conclusion: Updated results of Epitopes-HPV01 and 02 studies, as well as the pooled analysis, confirm mDCF as a standard treatment in patients with advanced SCCA.